Influence of Electronarcosis on Behavioral Responses, Blood Markers, and Fillet Properties of Silver Catfish (Rhamdia quelen). Issue 3 (16th March 2017) - Veit, Juliana C.; Piccolo, Jaqueline; Facco, Grasiela; Scherer, Aline F.; Baldisserotto, Bernardo; Koakoski, Gessi; Menezes, Charlene C.; Loro, Vania L.; Barcellos, Leonardo J. G.; Mello, Renius O.; Emanuelli, Tatiana
ABSTRACT: Behavioral responses, blood markers, and fillet properties were investigated after silver catfish exposure to different electric field strengths, frequency, and duration of electric current in the preslaughter stunning. All combinations of electric fields and frequencies were able to stun fish. Longer apparent stun was obtained at the intermediate electrical frequencies. High electric field strength detracted the texture of fillets. At least 5 s was required to stun fish, and longer exposure to electrical current did not prolong the apparent stun or damage fillet properties. Results indicate that silver catfish are relatively resistant to electronarcosis.